Enhanced cellular uptake and cytotoxicity of vorinostat through encapsulation in TPGS-modified liposomes - Farooq, Muhammad Asim; Xinyu, Huang; Jabeen, Amna; Ahsan, Anam; Seidu, Theodora Amanda; Kutoka, Perpetua Takunda; Wang, Bo (Colloids and surfaces, B, Biointerfaces, 2021)
[Display omitted] •TPGS modified liposomes were prepared using thin film hydration following the probe ultra-sonication method.•Surfaced-coated liposomal formulation enhanced the drug loading, encapsulation efficiency, solubility, and drug release profile.•TPGS coating on liposomes surface demonstrated a more toxic effect against breast cancer cells.•Modified liposomes also enhanced the qualitative and quantitative cellular uptake against MCF-7 cancer cells. Vorinostat (VOR) is known as one of the histone deacetylase inhibitors (HDACi) for cancer treatment, and the FDA approves it for cutaneous T cell lymphoma therapy. Poor solubility, permeability, and less anti-cancer activity are the main challenges for the effective delivery of VOR against various cancers. So, our team assumed that the surface-coated liposomes might improve the physicochemical properties of biopharmaceutics classification system class IV drugs such as VOR. The present study aimed to enhance the cytotoxicity and improve cellular uptake using TPGS-coated liposomes in breast cancer cells. Liposomes were fabricated by the film hydration following the probe ultra-sonication method. OR-LIPO and TPGS-VOR-LIPO showed an average particle size of 211.97 ± 3.42 nm with PDI 0.2168 ± 0.006 and 176.99 ± 2.06 nm with PDI 0.175 ± 0.018, respectively. TPGS-coated liposomes had better stability and revealed more than 80 % encapsulation efficiency than conventional liposomes. Transmission electron microscopy confirmed the TPGS coating around liposomes. Moreover, TPGS-coated liposomes enhanced the solubility and showed sustained release of VOR over 48 h. DSC and PXRD analysis also reveal an amorphous state of VOR within the liposomal formulation. MTT assay result indicates that the superior cytotoxic effect of surface-modified liposomes contrasts with the conventional and free VOR solution, respectively. Fluorescence microscopy and flow cytometry results also presented an enhanced cellular uptake of TPGS-coated liposomes against breast cancer cells, respectively. The current investigation's final results declared that TPGS-coated liposomes are promising drug carriers for the effective delivery of hydrophobic drugs for cancer therapy.